Sample size calculations for micro‐randomized trials in mHealth. (28th December 2015) - Liao, Peng; Klasnja, Predrag; Tewari, Ambuj; Murphy, Susan A.
Abstract : The use and development of mobile interventions are experiencing rapid growth. In "just‐in‐time" mobile interventions, treatments are provided via a mobile device, and they are intended to help an individual make healthy decisions 'in the moment, ' and thus have a proximal, near future impact. Currently, the development of mobile interventions is proceeding at a much faster pace than that of associated data science methods. A first step toward developing data‐based methods is to provide an experimental design for testing the proximal effects of these just‐in‐time treatments. In this paper, we propose a 'micro‐randomized' trial design for this purpose. In a micro‐randomized trial, treatments are sequentially randomized throughout the conduct of the study, with the result that each participant may be randomized at the 100s or 1000s of occasions at which a treatment might be provided. Further, we develop a test statistic for assessing the proximal effect of a treatment as well as an associated sample size calculator. We conduct simulation evaluations of the sample size calculator in various settings. Rules of thumb that might be used in designing a micro‐randomized trial are discussed. This work is motivated by our collaboration on the HeartSteps mobile application designed to increase physical activity. Copyright © 2015 John Wiley & Sons, Ltd.